2008
DOI: 10.1002/jnr.21661
|View full text |Cite
|
Sign up to set email alerts
|

The spleen contributes to stroke‐induced neurodegeneration

Abstract: Stroke, a cerebrovascular injury, is the leading cause of disability and third leading cause of death in the world. Recent reports indicate that inhibiting the inflammatory response to stroke enhances neurosurvival and limits expansion of the infarction. The immune response that is initiated in the spleen has been linked to the systemic inflammatory response to stroke, contributing to neurodegeneration. Here we show that removal of the spleen significantly reduces neurodegeneration after ischemic insult. Rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
223
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(240 citation statements)
references
References 45 publications
11
223
2
1
Order By: Relevance
“…As stated above, removal of the spleen either surgically 8,10 or by radiation significantly reduces infarct volume 9 after MCAO, suggesting that the elimination of splenocytes by any means may result in protection from ischemic injury. Splenectomy has also proven to be beneficial in other types of brain injuries, such as hemorrhagic stroke and traumatic brain injury.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…As stated above, removal of the spleen either surgically 8,10 or by radiation significantly reduces infarct volume 9 after MCAO, suggesting that the elimination of splenocytes by any means may result in protection from ischemic injury. Splenectomy has also proven to be beneficial in other types of brain injuries, such as hemorrhagic stroke and traumatic brain injury.…”
Section: Introductionmentioning
confidence: 79%
“…Conversely, multiple groups (including our unpublished data) have showed that proinflammatory macrophages contribute to neurodegeneration and that splenectomy 2 weeks before stroke is neuroprotective. [6][7][8] The authors state that the lack of neuroprotection with splenectomy can be attributed to the time splenectomy was performed, immediately before middle cerebral artery occlusion (MCAO) in their case, which does not allow the body time to adapt or equilibrate to the loss of the spleen and to allow turnover of circulating splenocytes. However, Ostrowski et al 9 showed that nonsurgical irradiation of the spleen immediately after experimental stroke reduces infarct by abrogating deployment of spleen cells to the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, after over 20 years of innovative research, the events triggering motor neuron death in SMA remain elusive. It is interesting to note that lymphoid organs, and more specifically the spleen, may actively participate in the process of neurodegeneration 39. ALS, an adult onset motor neuron disorder, has received attention from the SMA community for their possible common molecular ties in disease pathogenesis 40.…”
Section: Status Of Neuroinflammation In Als and Smamentioning
confidence: 99%
“…In parallel to events within the brain, lymphocytes, neutrophils, and monocytes traffic to the brain from the periphery and contribute to further neuronal damage. The spleen is a principal reservoir that reduces in size after stroke, releasing inflammatory cells and cytokines into the circulation [8][9][10][11][12][13][14][15]. In addition, the bone marrow mobilizes a subpopulation of multipotent stem cells into the peripheral blood following stroke, which is then directed towards the brain, as well as peripheral organs such as the spleen [16].…”
Section: Central and Peripheral Mechanisms Of Inflammationmentioning
confidence: 99%
“…There are many studies establishing a role for the spleen in the inflammatory processes following ischemia-perfusion injury of various organs or trauma, with some even showing the importance of splenectomy in reducing the proinflammatory response [13,64,65]. As splenectomy is not feasible in patients with stroke, a novel method such as controlling poststroke inflammatory response by enhancing the CD25 bright subpopulation of regulatory T cells could prove useful [66].…”
Section: Targeting the Spleen As A Therapeutic Strategymentioning
confidence: 99%